Weaker Links Between Zonal Convective Clustering and ITCZ Width in Climate Models Than in Observations. Issue 22 (21st November 2020) - Popp, Max; Lutsko, Nicholas J.; Bony, Sandrine
Abstract: Strong links are seen in observations between convective clustering and several properties of the Intertropical Convergence Zone (ITCZ). These links suggest that biases in how climate models simulate the ITCZ may be related to model biases in convective clustering or that there may be biases in how models represent the relationship between clustering and the ITCZ. We investigate these issues by analyzing convective clustering, and the link between clustering and ITCZ properties in 18 climate models. We find that the links between variability in convective clustering and variability of ITCZ properties are generally weaker and less robust in models than in observations. By contrast, model biases in the climatological convective clustering explain a substantial fraction of the climatological double‐ITCZ bias, though they do not explain biases in the climatological ITCZ width. Plain Language Summary: The tropical deep convection that forms deep and strongly precipitating clouds organizes in various patterns and shapes within a narrow rain band that spans the globe in the tropics. The form of organization of this tropical deep convection has been shown to covary with several other properties of the rain band, such as its meridional width, in observations. This raises the question whether climate models can represent these links between the organization of convection and the rain‐band properties. It is found that models simulate such a link between the spatial concentration of the deep convection and the width of the rain band, but this link is generally too weak. The models are unable to simulate the observed link between the concentration of the deep convection and the double‐peak structure of the rain band. By contrast, the biases in mean concentration of the deep convection cannot explain the biases in the meridional width of the rain band, but explain a substantial fraction of the biases in the double‐peak structure of the rain band. Key Points: Climate models underestimate the link between zonal convective clustering and the ITCZ width Model biases in convective clustering explain double‐ITCZ biases, but not ITCZ width biases Several factors may play a role in linking convective clustering and the ITCZ width, but no dominant mechanism was found